Effect of SSP – 11 on Weight and Tissue Composition of 4th Instar Larvae of Silkworm, Bombyx mori - Venkata Rami Reddy, K.; Sashindran Nair, K.; Magadum, S. Β.; Datta, R. Κ. (ENTOMOLOGIA HELLENICA, 1993)
The anti-juvenoid, SSP-11 ((E) 4-chloro-a, a, a-trifluro-N [ 1 (1 H-imidazole- 1 –y1)- 2-propoxy ethylyledene] O, toludine) was used to induce trimoulters from tetramoulter larvae of the silkworm, Bombyx mori (race NB7). The compound was fed for two days through an artificial diet at the concentration of 200 ppm to newly ecdysed 4th stadium larvae. Body and silkgland fresh weight were recorded daily in the 4th larval stadium and protein profiles of haemolymph, fat body and silkgland were determined at the end of the stadium. In larvae treated with SSP-11, feeding period in stadium 4 was prolonged by 3-4 days and 80-85% of the larvae started to spin as trimoulters. Eight and thirty fold increases in the larval body and silkgland weights respectively were the result of SSP-11. Further, total proteins, total carbohydrates, glycogen and nucleic acid (DNA & RNA) also increased. The activity levels of alanine aminotransferase and aspartate aminotransferasc increased significantly than in the control indicating increased mobilization of aminoacids into transamination activities.